2021
DOI: 10.1007/s40256-021-00496-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of a CYP2C19 Genotype-Guided Strategy in Patients with Acute Myocardial Infarction: Results from the POPular Genetics Trial

Abstract: IntroductionThe POPular Genetics trial demonstrated that a CYP2C19 genotype-guided P2Y 12 inhibitor strategy reduced bleeding rates compared with standard treatment with ticagrelor or prasugrel without increasing thrombotic event rates after primary percutaneous coronary intervention (PCI). Objective In this analysis, we aimed to evaluate the cost effectiveness of a genotype-guided strategy compared with standard treatment with ticagrelor or prasugrel. Methods A 1-year decision tree based on the POPular Geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…By applying a genotype-guided strategy in ACS patients treated with ticagrelor or prasugrel, 60-70% of patients can be de-escalated to clopidogrel, which results in reduced side effects and lower costs. [28][29][30] Our findings match the POPular Genetics trial costeffectiveness analyses. 29 This study showed that a de-escalation strategy has the potential to yield cost savings of more than €300 per patient in the first year after ACS.…”
Section: Cost-effectivenesssupporting
confidence: 80%
“…By applying a genotype-guided strategy in ACS patients treated with ticagrelor or prasugrel, 60-70% of patients can be de-escalated to clopidogrel, which results in reduced side effects and lower costs. [28][29][30] Our findings match the POPular Genetics trial costeffectiveness analyses. 29 This study showed that a de-escalation strategy has the potential to yield cost savings of more than €300 per patient in the first year after ACS.…”
Section: Cost-effectivenesssupporting
confidence: 80%
“…For testing to be cost saving, the de-escalation rate needs to improve (from 20% to at least 40%), and/or the duration of treatment impact would have to increase (for example by testing earlier or testing only chronic users). Earlier studies on genotype-guided P2Y 12 inhibitor therapy selection showed cost-effectiveness based on the premise of a 100% de-escalation rate [ 67 , 68 , 69 , 70 ]. This assumption has been deemed unrealistic, but our study shows that less than 100% de-escalation can still suffice to obtain cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 13 included studies, only two studies showed that universal ticagrelor was cost-effective when compared to genotype-guided therapy. They concluded that genotype-guided therapy is cost-effective in patients with ACS undergoing PCI ( 96 , 97 ). Most recently, Claassens et al conducted a cost effectiveness analysis of genotype guided therapy based on the POPular Genetics trial ( 97 ).…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…They concluded that genotype-guided therapy is cost-effective in patients with ACS undergoing PCI ( 96 , 97 ). Most recently, Claassens et al conducted a cost effectiveness analysis of genotype guided therapy based on the POPular Genetics trial ( 97 ). A base-case analysis was performed for a cohort of 1,000 patients showed that genotype guided therapy was dominant, and resulted in a gain of 8.98 QALYs, and cost saving of €725,550.69 when compared to universal ticagrelor or prasugrel ( 97 ).…”
Section: Cost Effectivenessmentioning
confidence: 99%